The Relationship Between Total Reward Management and Employee Performance: A Case Study of Oil & Gas Company in Indonesia - Ayu Astria Putri; Achmad Fajar Hendarman (Yayasan Riset dan Pengembangan Intelektual, 2025)
These objectives provide a structured framework for in-depth analysis that focuses on spesific objectives of the research: determining the relationship between Total Reward Management and employee performance, determining the factors of Total Reward Management that had significant relationship to employees, and giving Recommendation of Total Reward Management Package to increase employee performance in PT Petroleum Upstream Corporation. This study uses a mixed-methods approach, combining surveys of 547 employees and focus group discussions with management. Quantitative data were analyzed using descriptive statistics, reliability tests, and regression analysis, while qualitative data were examined through thematic and root cause analysis to explore the implementation and impact of Total Reward on employee performance. The findings show that Total Reward Management has a positive and significant relationship with employee performance at PT Petroleum Upstream Corporation, fulfilling the first research objective. Each component of total rewards including compensation, benefits, well-being, development, and recognition also demonstrated a significant impact on employee performance, with well-being, recognition, and benefits showing the strongest correlation, thereby addressing the second objective. Based on both quantitative and qualitative analysis, this study recommends enhancing non-financial rewards, particularly in well-being and recognition programs, while maintaining a balanced reward mix. These actionable recommendations support the third objective by offering practical strategies to improve employee performance through an optimized Total Reward Management package.